Visualizing GABA A Receptor Trafficking Dynamics with Fluorogenic Protein Labeling. Issue 1 (4th May 2020) - Lombardi, Jacob P.; Kinzlmaier, David A.; Jacob, Tija C.
Abstract: It is increasingly evident that neurotransmitter receptors, including ionotropic GABA A receptors (GABAARs), exhibit highly dynamic trafficking and cell surface mobility. Regulated trafficking to and from the surface is a critical determinant of GABAAR neurotransmission. Receptors delivered by exocytosis diffuse laterally in the plasma membrane, with tethering and reduced movement at synapses occurring through receptor interactions with the subsynaptic scaffold. After diffusion away from synapses, receptors are internalized by clathrin‐dependent endocytosis at extrasynaptic sites and can be either recycled back to the cell membrane or degraded in lysosomes. To study the dynamics of these key trafficking events in neurons, we have developed novel optical methods based around receptors containing a dual‐tagged γ2 subunit (γ2pHFAP) in combination with fluorogen dyes. Specifically, the GABAAR γ2 subunit is tagged with a pH‐sensitive green fluorescent protein and a fluorogen‐activating peptide (FAP). The FAP allows receptor labeling with fluorogen dyes that are optically silent until bound to the FAP. Combining FAP and fluorescent imaging with organelle labeling allows novel and accurate measurement of receptor turnover and accumulation into intracellular compartments under basal conditions in scenarios ranging from in vitro seizure models to drug exposure paradigms. Here we provide a protocol to track and quantify receptors in transit from the neuronal surface to endosomes and lysosomes. This protocol is readily applicable to cell lines and primary cells, allowing rapid quantitative measurements of receptor surface levels and postendocytic trafficking decisions. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Preparation of cortical neuronal cultures for imaging assays Basic Protocol 2 : Surface receptor internalization and trafficking to early endosomes Basic Protocol 3 : Measurement of receptor steady state surface level, synaptic level, and lysosomal targeting